Sistema solar fotovoltaico conectado á rede : uma análise de viabilidade econômica - Silva, Waldeny José da (2020)
The present work presents an economic feasibility analysis of the installation of photovoltaic systems connected to the grid (SFCR) in consumer units of group A and group B, so that the research and development of the calculations involved can be used to motivate students in mathematics classes directed to basic education classes as recommended by the reference documents for Mato Grosso (DRC-MT). For this purpose, the composition of the energy tariff was discussed and photovoltaic systems capable of meeting the energy demand of two consumer units, both located in Mato Grosso, were dimensioned, each belonging to one of the groups mentioned above. The sizing was done based on their respective annual consumption averages. Along with the topics studied, examples of lesson planning and some learning objectives that can be addressed are suggested. Based on a detailed quotation of prices and equipment and services, the total value of the installation and maintenance of the SFCR was determined for each of the systems mentioned. Then, an estimate of the expenses with electricity was made without using the SFCR. Finally, the values obtained are compared, and demonstrated using tables and graphs. The results obtained indicate that the investment compensation takes about 7 years, in the case of units in group B and 9 years in the case of consumer units in group A. As for the work in the classroom, the possibility of using this material is evident when taking into account the suggestions present in the DRC-MT due to the fact that electricity is such a common theme in the students’ daily lives.